PENGARUH RASIO UTANG, LABA PER SAHAM DAN RASIO PENGEMBALIAN EKUITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN LQ45 YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015-2019 - Friska Nadya; Linna Ismawati (Manis: Jurnal Manajemen dan Bisnis, 2020)
This research purpose to determine the impact of the DER, EPS and ROE on the LQ45 firm value listed on the Indonesia Stock Exchange for the 2015-2019 period. This research used descriptive and verification methods with a quantitative approach. This research used secondary data taken from 2015 -2019 financial reports and 7 companies, with a total of 35 data. This study used the multiple linear regression using SPSS 25 software. The results of this research show that partially DER has a significant effect on Firm Value, EPS has no significant impact on firm value and ROE has a significant positive impact on LQ45 firm value. And the DER, EPS and the ROE have a significant impact simultaneously on Firm Value.